Autonomous Foraging of Virtual Characters with a Constructivist Cognitive Architecture - Rocha, Victor; Brandao, Louise; Nogueira, Yuri Lenon Barbosa; Cavalcante-Neto, Joaquim; Vidal, Creto (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2021: Anais do XXIII Simpósio de Realidade Virtual e Aumentada, 2021)
Immersive experiences in virtual reality simulations require natural-looking virtual characters. Autonomy researchers argue that only the agent's own experience can model their behavior. In this regard, the Constitutive Autonomy through Self-programming Hypothesis (CASH) is an effective approach to implement this model. In this paper, we contribute to the discussion of CASH within dynamic and continuous environments by developing mechanisms of memory decay, contradiction penalty, and relative valence. Such improvements aim to see how the agent might continuously reevaluate their learned schemas. The results show that our agents were able to develop autonomously into performing plausible behaviors, despite the changing environment.